2014
DOI: 10.1007/s10152-014-0389-0
|View full text |Cite
|
Sign up to set email alerts
|

Transitions in sandflat biota since the 1930s: effects of sea-level rise, eutrophication and biological globalization in the tidal bay Königshafen, northern Wadden Sea

Abstract: Conspicuous macrozoobenthos and vegetation of intertidal sandflats in Königshafen (Island of Sylt, SE North Sea) were mapped in 1932, 1988 and 2008. Higher water levels since the 1930s with a concomitant increase in tidal dynamics are assumed to have weakened sediment stability. This dissolved the distinctly banded macrobenthic zonation of the 1930s. Near high water level, cyanobacterial mats with associated beetles, belts of the mudshrimp Corophium volutator and the seagrass Zostera noltii have vanished, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 50 publications
1
14
0
Order By: Relevance
“…For example, long-term investigations of fish, plankton, and benthos in the Western English channel found indications for regime shifts during the last century caused by fishing pressures (Southward et al 2005). Other studies investigated the Southern and central parts of the North Sea and found similar evidence for long-term changes in benthic community structure attributed to fishing (Pennington et al 1998;Rumohr and Kujawski 2000;Bradshaw et al 2002;Robinson and Frid 2008) and nutrient loading (Schroeder 2005;Schumacher et al 2014). Likewise, a series of historical studies from the eastern parts of the North Sea documented remarkable long-term changes in benthic communities attributed to trawling pressure and eutrophication (Rosenberg and Möller 1979;Pearson et al 1985;Rosenberg et al 1987;Göransson 2002).…”
Section: Communicated By D M Patersonmentioning
confidence: 92%
“…For example, long-term investigations of fish, plankton, and benthos in the Western English channel found indications for regime shifts during the last century caused by fishing pressures (Southward et al 2005). Other studies investigated the Southern and central parts of the North Sea and found similar evidence for long-term changes in benthic community structure attributed to fishing (Pennington et al 1998;Rumohr and Kujawski 2000;Bradshaw et al 2002;Robinson and Frid 2008) and nutrient loading (Schroeder 2005;Schumacher et al 2014). Likewise, a series of historical studies from the eastern parts of the North Sea documented remarkable long-term changes in benthic communities attributed to trawling pressure and eutrophication (Rosenberg and Möller 1979;Pearson et al 1985;Rosenberg et al 1987;Göransson 2002).…”
Section: Communicated By D M Patersonmentioning
confidence: 92%
“…In the more distal German Wadden Sea, a reduction of phytoplankton biomass was not seen until after nitrogen loads were also reduced. Despite the apparent abatement of eutrophication the ecosystem had not, however, returned to its previous state largely because of the changes in this intertidal ecosystem related to sea-level rise and invasions of non-indigenous species, including the marsh grass, Spartina anglica, and the introduced oyster Crassostrea gigas, which has supplanted mussel beds (Schumacher et al, 2014).…”
Section: North Seamentioning
confidence: 99%
“…volutator density consistently leads to reduced organic matter consumption (Fig 3A and 3C) raises questions about the ability of mudflats to assimilate organic waste and remineralise the contained nutrients if populations of this species collapse. Such concerns are exacerbated by the fact that various historic populations of the species have collapsed in recent years, notably in the Wadden Sea [53,54]. If C .…”
Section: Discussionmentioning
confidence: 99%